Coke‐Tolerant Gadolinium‐Promoted HZSM‐5 Catalyst for Methanol Conversion into Hydrocarbons. Issue 9 (24th February 2017) - Kim, Sungtak; Kim, Yong Tae; Hwang, Ahron; Jun, Ki‐Won; Kwak, Geunjae
Abstract: The role of Gd as a coke inhibitor was studied for the methanol‐to‐hydrocarbons reaction. It was revealed that thin films of gadolinium oxide covered the ZSM‐5 crystals and that the Gd atoms that were uniformly dispersed on the surface enhanced the basicity of the parent ZSM‐5. These synergetic effects improved the durability of the acidic function and diminished the growth of coke precursors, which resulted in an increased lifetime of the catalyst. Abstract : Release your inhibitions : The role of Gd as a coke inhibitor is studied for the methanol‐to‐hydrocarbons reaction. Thin films of gadolinium oxide cover the ZSM‐5 crystals and decrease the rate of formation of coke species, and uniformly distributed Gd atoms in the pores of ZSM‐5 help to modify the surface acid–base properties. These synergetic effects help to improve the lifetime of the H‐ZSM‐5catalyst.